CONTEMPORARY ISSUES IN LITERARY STUDIES AND TRANSLATION IN THE GLOBAL DIGITAL ERA - ALLABERGENOVA, Intizor Kadamovna (The Lingua Spectrum, 2025)
This study explores contemporary issues in literary studies and translation within the context of globalization and rapid digital transformation. The research aims to examine how cultural identity, intertextuality, and authorial style are preserved or altered during translation, especially when transferring culturally loaded literary texts. Methodologically, the study employs comparative textual analysis, descriptive translation studies, and elements of corpus linguistics to identify shifts and patterns occurring in modern translation practices. The results reveal that the increasing use of artificial intelligence tools, including machine translation systems, significantly influences the translator’s role, accuracy, and interpretive responsibility. While digital technologies support efficiency, they often fail to convey subtle literary nuances, figurative meanings, and culturally specific expressions. The discussion highlights the need for new translator competencies, ethical considerations, and hybrid translation models combining human expertise with AI assistance. The study concludes that the modernization of translation education, the integration of corpus-based approaches, and the reconsideration of literary analysis frameworks are essential for addressing current challenges in both fields.